Applications of Polyhedral Oligomeric Silsesquioxanes - Hartmann-Thompson, Claire; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
The commercial availability and decreasing cost of polyhedral oligomeric silsesquioxanes in recent years has opened up the field to everybody who wishes to apply these unique properties in their own technologies. This is the first book to provide a comprehensive overview of these applications, and covers the synthesis, characterization and history of polyhedral oligomeric silsesquioxanes, their use as metallasilsesquioxane catalysts, their effect upon polymer properties and plastics performance, and their use in superhydrophobic nanocomposites, and electronics, energy, space and biomedical applications. "Applications of Polyhedral Oligomeric Silsesquioxanes" is a valuable reference for those working across a range of disciplines, including chemists, materials scientists, polymer physicists, plastics engineers, surface scientists, and anybody with a commercial or academic interest in plastics, composite materials, space materials, dental materials, tissue engineering, drug delivery, lithography, fuel cells, batteries, lubricants, or liquid crystal, LED, sensor, photovoltaic or biomedical devices.
Keywords: Chemistry; Chemistry, inorganic; Chemistry, Organic; Materials; Nanotechnology; Chemistry; Organic Chemistry; Nanotechnology; Inorganic Chemistry; Materials Science, general